2012
DOI: 10.1002/jcu.21987
|View full text |Cite
|
Sign up to set email alerts
|

Intima‐medial thickness homogeneity in the common carotid artery: Measurement method and preliminary clinical study

Abstract: IMTH is a promising approach for the assessment of atherosclerosis, in addition to conventional IMT measurement. Further clinical studies are needed to assess its clinical usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Carotid IMR measured by the software system is consistent with the results of manual measurement in previous studies . The Bland‐Altman test showed that the measurement parameters were repeatable and could stably reflect the morphologic changes of the carotid intima‐media.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Carotid IMR measured by the software system is consistent with the results of manual measurement in previous studies . The Bland‐Altman test showed that the measurement parameters were repeatable and could stably reflect the morphologic changes of the carotid intima‐media.…”
Section: Discussionsupporting
confidence: 84%
“…Carotid IMR measured by the software system is consistent with the results of manual measurement in previous studies. 7 The Bland-Altman test showed that the measurement parameters were repeatable and could stably reflect the morphologic changes of the carotid intima-media. Studies by Ishizu et al 12 and Schmidt-Trucksäss et al 13 demonstrated that carotid IMR was significantly increased in patients with coronary heart disease compared with healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies use cIMT ≥ 1 mm as evidence of arterial thickening (Cheng et al, 2012). However, there is controversy regarding the cutoff point for atherosclerotic plaque.…”
Section: Assessment Of Atherosclerotic Plaquementioning
confidence: 99%
“…Our objective was to develop a tissue classification technique that characterizes the early changes in the far wall region (FWR) of the common carotid artery (CCA) in order to identify patients whose features are (“ Sym ” class ) or not (“ Asym ” class ) associated with symptoms, before the plaque onset, because studies have shown that progressive atherosclerotic lesions start with intimal thickening . We used IMT variability, or IMTV poly , as one of these features . Manual measurement of IMT from B‐mode images is time‐consuming and prone to intra‐ and inter‐observer variability.…”
mentioning
confidence: 99%